Species richness of mammals from the vicinity of Salina Sruz, coastal Oaxaca, México - CERVANTES, FERNANDO A.; YÉPEZ MULIA, LILIAN (Anales del Instituto de Biología serie Zoología, 2009)
THE SPECIES RICHNESS OF MAMMALS FROM THE VICINITY OF SALINA CRUZ, OAXACA, MEXICO, WAS SURVEYED. SISTY-FIVE SPECIES OF SPECIES, OF NATIVE TERRESTRIAL MAMMALS IN THE REGION, BELONGING TO 54 GENERA, 24 FAMILIES, AND 8 ORDERS WERE FOUND. TWO SPECIES ARE ENDEMIC, ONE TO OAXACA, AND THE OTHER TO MEXICO. FIVE EXOTIC SPECIES(THREE MURINE RODENTS, ONE FELID, AND ONE CANID) COMPLEMENTED THE LIST. MOST TAXA ARE OF TROPICAL AFFINITY. THE SPECIES RICHNESS OF MAMMALS OF THE STUDY AREA TURNED OUT TO BE LARGE AND DIVERSE. THIS SURVEY INCREASED THE MAMMAL RECORDS FOR THIS REGION OF COASTAL OAXACA. HOWEVER, MORE RESEARCH IS NEEDED TO: 1, RECORD OTHER SPECIES EXPECTED TO BE PRESENT, AND 2 EVALUATE THE HUMAN FACTORS THAT MAY BE THREATENING THE MAMMAL SPECIES RICHNESS OF THE VICINITY OF SALINA CRUZ.